Islamic Republic of Iran : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Iran. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that economic activity in Iran has slowed down significantly since the fourth quarter of 2014/15 owing to sharp decline in global oil prices, tight corporate and bank balance sheets, and postponed consumption and investment decisions ahead of the expected lifting of economic sanctions. Twelve-month (point-to-point) inflation has declined to about 10 percent in recent months, largely reflecting lower food and beverage inflation, and the inflation rate is expected to remain close to 14 percent by year-end. Prospects for 2016/17 are brighter, owing to the prospective lifting of economic sanctions.